Precariousness, Diabetes Control and Complications in French Guiana - Linière, Samuel; Nacher, Mathieu; Drak Alsibai, Kinan; Mergeayfabre, Mayka; Hafsi, Nezha; Charpin, Aurelie; Misslin-Tritsch, Caroline; Carod, Jean-François; Aurelus, Jean Markens; De Toffol, Bertrand; Ntoutoum, André; Kakamba, John Bukasa; et al. (Frontiers in Endocrinology, 2022)
Aims: The social parameters of an individual impact the incidence of cardiovascular diseases. French Guiana, an overseas French territory with a lower standard of living than France, has a prevalence of diabetes mellitus that is twice that of mainland France. In this context we aimed to study the relation between precariousness, diabetes complications and glycemic control. Methods: A multicenter prospective cohort was conducted since May 2019. 1243 patients were included and their outcomes and history were compared according to their EPICES (Evaluation of Precariousness and Inequalities in Health in Health Examination Centers) score, a score that measures social isolation and precariousness. Results: 73.3% of the sample was considered precarious. There was a significant difference in Glycated Haemoglobin between the two groups (8.3% (67 mmol/l) vs 8.8% (73mmol/l)). Retinopathy and infections were significantly more frequent among the deprived. Survival analysis showed an increased risk of stroke (incidence rate at 3.0 vs 4.2; Hazard Ratio=1.9 (95%CI=1-3.5), p=0.046) and infections (incidence rate at 9.8 vs 13.8; Hazard Ratio=1.5 (95%CI=1.1-2.1), p=0.02) among the deprived. Conclusions: Precariousness is a risk factor for retinal, arterial and infectious complications in patients with diabetes mellitus in French Guiana. Such inequalities suggest health system adaptations to reach socially deprived or isolated persons.